Cobalt nickel boride as electrocatalyst for the oxidation of alcohols in alkaline media. (2nd March 2023) - Braun, Michael; Chatwani, Mohit; Kumar, Piyush; Hao, Yun; Sanjuán, Ignacio; Apostoleri, Ariadni-Aikaterini; Brix, Ann Cathrin; Morales, Dulce M; Hagemann, Ulrich; Heidelmann, Markus; Masa, Justus; Schuhmann, Wolfgang; et al.
Abstract: A mixed Co and Ni boride precursor was synthesized via chemical reduction and subsequently annealed at 400 or 500 °C with or without prior addition of the monomer benzoxazine (BO). The resulting mixed CoNiB materials were investigated as electrocatalysts for three alcohol oxidation reactions (AOR) in alkaline electrolyte: the oxidation of glycerol (GOR), ethylene glycol (EGOR) and ethanol (EOR). Comparison of the rotating disk electrode (RDE) cyclic voltammograms for the different catalysts revealed that CoNiB annealed at 500 °C without the addition of BO exhibited the lowest overpotentials in AORs at 10 mA cm −2, promoting GOR at 224 ± 6 mV lower potential compared to OER. When pyrolysis was conducted at 400 °C, the BO-containing catalyst showed a significant increase in the electrocatalytic activity for the AORs compared to the CoNiB catalyst only. The product selectivity on the different catalysts was investigated in a batch-type reactor with flow recirculation revealing formate as the main oxidation product during GOR and EGOR with faradaic efficiencies (FE) in a range of 60%–80%, while acetate was obtained during EOR (FE ∼ 85%–90%). The electrode potential, electrolyte composition and the type of ionomer were explored with respect to their influence on the GOR selectivity. The use of different ionomers resulted in significant differences in the activity trends between RDE and the batch-type reactor with flow recirculation measurements, indicating a strong influence of the two different substrates used, namely glassy carbon and carbon paper on the catalyst formation and thus on the recorded electrochemical activity.